Assessing executive functioning in higher education: development and structural validation of a new self-report scale - Zamora-Lugo, Samuel; Reynoso-Alcántara, Vicenta; Sanchez-Lopez, Javier; Vergara-Lope, Samana; Ocampo-Gómez, Elizabeth; García-Gomar, María Luisa; Torres-González, Cynthia; Avecilla-Ramírez, Gloria Nélida; Carbajal-Valenzuela, Cintli Carolina; Calderón, Melissa; Vázquez-Moreno, Almitra; Flores-González, Rubén; et al. (Frontiers in Psychology, 2025)
IntroductionExecutive functions are essential cognitive processes that support goal-directed behavior, self-regulation, and academic performance in higher education. However, few assessment tools provide psychometrically validated and contextually appropriate measures for university populations.MethodsThis study presents the development and structural validation of the Executive Functions Scale in Higher Education (EFEES), a self-report instrument designed to evaluate university students’ self-perceived executive functioning. The scale was developed through a theory-driven approach that defined 10 core dimensions, validated behavioral indicators with expert input, and generated positively framed items tailored to the academic context. A total of 1,538 undergraduate students from 12 Mexican universities (M = 20.6, SD = 1.69) completed the instrument.ResultsExploratory and confirmatory factor analyses supported a four-factor structure—organization, self-control, attentional and inhibitory control, and planning and time management—accounting for 38% of the variance. The scale demonstrated high internal consistency across factors (Cronbach’s α = 0.84–0.97; McDonald’s ω = 0.84–0.99).DiscussionFindings confirm the structural validity and reliability of the EFEES and highlight its utility in identifying executive-function profiles associated with students’ cognitive and academic development. Although initially validated in a Mexican sample, the EFEES was conceptually designed for cross-cultural applicability and can be adapted to diverse higher education contexts. The scale offers a theoretically grounded, psychometrically sound, and practically relevant tool for research and educational interventions aimed at supporting student success.